Positive solutions for nonlinear difference equations involving the p-Laplacian with sign changing nonlinearity - Yanbin Sang (Electronic Journal of Differential Equations, 2009)
By means of fixed point index, we establish sufficient conditions for the existence of positive solutions to p-Laplacian difference equations. In particular, the nonlinear term is allowed to change sign.